The political economy of gender inequality in South Africa: Why unpaid care work should be recognised in economic policy - Delle, Donne Gianni (School of Economics, 2022)
This study aims to present a feminist political economy framework within which to understand the nature of gender inequality in South Africa. Particular attention is placed on the role of unpaid care work as this work is shown to be predominantly undertaken by women and still goes unrecognised, despite its importance in the prevailing capitalist economic system. The paper argues that the lack of recognition of unpaid care work in mainstream economics which informs policy making is a source of gender inequality in the South African context. Furthermore, it argues that the government's fiscal response to the COVID-19 pandemic should be refused on the basis that it will exacerbate gender inequality as a result of women's greater role in social reproduction. The paper is structured as follows. In part one, unpaid care work is theoretically grounded within Marxism and social reproduction feminism literature. This is primarily done in order to illustrate two characteristics of unpaid care work. Firstly, that despite being uncompensated for, care work is a critical component of reproducing the labour force and is therefore a core component of the prevailing capitalist modes of production. Secondly, that unpaid care work is a highly gendered phenomenon. The role of underlying patriarchal norms in entrenching the gendered nature of unpaid care work is also considered in this section. In section two, neoliberalism and financialisation are discussed in the South African context and in light of South Africa's historical industrial development. It is shown that working class conditions in post-apartheid era have deteriorated and that, due to the feminization of unpaid care work, women have been disproportionately affected by these developments. In section three, the gendered implications of the COVID-19 pandemic and of the government's planned austerity in response to it are considered. Evidence is presented in order to show how the pandemic has increased gender inequality, as it has had particularly negative consequences for the paid and unpaid care sectors, which are overrepresented by women. Thereafter, it is shown how austerity, specifically due to budget cuts to education, health care and social grants, will exacerbate gender inequality further due to the feminisation of care responsibilities. On this basis, it is argued that the government's fiscal response to the pandemic is not gender neutral and should be refused. A human rights based approach is argued to be more aligned with the state's duties under the constitution.